(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Background and Objective: e-Monev is a monitoring innovation to find out how the impact of the COVID-19 pandemic has been on 6 indicators of nutrition programs related to stunting and proposed recommendations. This activity involved 17 partner tertiary institutions that assisted 260 District/City Health Offices in collecting data, conducting analysis, and compiling documents. The e-Monev activities aim to produce: (1) A web-based e-Monev system using routine e-PPGBM data for monitoring conducted by the Ministry of Health, Provincial Health Offices, and district/city Health Offices; and (2) Analysis at the District/City level in the form of three documents prepared, namely 1) Impact analysis document, 2) Policy analysis document, and 3) Policy brief in the form of recommendations for various parties. Implementation: There are 6 indicators in e-PPGBM that are used 1) Weighing toddlers at Posyandu, 2) Providing PMT for toddlers, 3) Exclusive breastfeeding program, 4) Vitamin A supplementation, 5) Feeding infants and children (PMBA), and 6 ) Integrated management of sick toddlers (IMCI). The e-PPGBM data used has been verified by the Directorate of Nutrition, Directorate General of Public Health, Ministry of Health of the Republic of Indonesia. The verified data is managed and presented in the form of a Dashboard. The data on the web is analyzed by the Health Service accompanied by a university assistant, and presented in the form of an impact analysis. The results of the impact analysis are followed by policy analysis and policy recommendations for various parties which are written in the form of a policy brief document. Results: (1) Web e-Monev system, including Dashboard, can be used; (2) An impact analysis was carried out by some of the District Health Offices with the results: Toddler weighing is the indicator most affected by the COVID-19 pandemic (86%). The exclusive breastfeeding indicator is the indicator with the least amount of data, namely 41.15% of districts/cities have no data, and vitamin A supplementation is the least affected indicator (60%). The implementation of PMBA and MTBS varies widely, including implementing new normal habits and utilizing social media for education. The document is made by the city district health office together with the companion. The implementation team also consulted with assistants regarding documents that had not been fulfilled by the health office in the hope that it would make it easier for the health office to carry out the analysis. So that currently the total is 100% Document 1, 100% Document 2, and 100% Document 3. Recommendation: Technically the e-Monev system can already be used with a Dashboard which can be updated in real-time. It is hoped that this e-Monev system can be used continuously with routine e-PPGBM data updates to see the impact of the COVID-19 Pandemic. It is recommended that training be conducted for the Provincial Health Office and stakeholders in the District/We to use it more effectively. In general, the recommended COVID-19 recovery policies are: 1) Strengthening commitment, regulation, and coordination across sectors, 2) Strengthening nutrition surveillance and data management during a pandemic, 3) Optimizing affected nutrition programs, 4) Facilitating infrastructure for adaptation to new normal habits, including providing health protection for TPG and cadres working in the community, 5) improving infrastructure and internet access.